MEFV gene polymorphisms and TNFRSF1A mutation in patients with inflammatory myopathy with abundant macrophages. (1st October 2014) - Fujikawa, K; Migita, K; Shigemitsu, Y; Umeda, M; Nonaka, F; Tamai, M; Nakamura, H; Mizokami, A; Tsukada, T; Origuchi, T; Yonemitsu, N; Yasunami, M; et al.
Summary: Inflammatory myopathy with abundant macrophages (IMAM) has recently been proposed as a new clinical condition. Although IMAM shares certain similarities with other inflammatory myopathies, the mechanisms responsible for this condition remain unknown. Patients with familial Mediterranean fever (FMF) and tumour necrosis factor receptor-associated periodic syndrome (TRAPS) also often develop myalgia. We therefore investigated the polymorphisms or mutations of MEFV and TNFRSF1A genes in patients with IMAM to identify their potential role in this condition. We analysed the clinical features of nine patients with IMAM and sequenced exons of the MEFV and TNFRSF1A genes. The patients with IMAM had clinical symptoms such as myalgia, muscle weakness, erythema, fever and arthralgia. Although none of the patients were diagnosed with FMF or TRAPS, seven demonstrated MEFV polymorphisms ( G304R, R202R, E148Q, E148Q-L110P and P369S-R408Q ), and one demonstrated a TNFRSF1A mutation ( C43R ). These results suggest that MEFV gene polymorphisms and TNFRSF1A mutation are susceptibility and modifier genes in IMAM.